Network Meta-Analysis of Perioperative Analgesic Effects of Different Interventions on Postoperative Pain After Arthroscopic Shoulder Surgery Based on Randomized Controlled Trials - Jiangping, Wu; Xiaolin, Quan; Han, Shu; Zhou, Xiaolan; Mao, Nie; Zhibo, Deng; Ting, Gong; Shidong, Hu; Xiangwei, Li; Xin, Yuan; Guoyin, Shu (Frontiers in Medicine, 2022)
Background: Shoulder arthroscopic surgery is a common surgical method used in orthopaedics. However, severe postoperative pain can significantly limit the early joint movement of patients and adversely affect the impact of the surgery. At present, there is no consistent and effective analgesic scheme for the management of postoperative pain after arthroscopic surgery of shoulder. Purpose: To search for the most effective analgesia scheme to control pain in the perioperative period of arthroscopic surgery of shoulder. Study Design: Network meta-analysis. Method: We searched 5 different databases (Medline, PubMed, Embase，Web of Science, and the Cochrane Library) from January 2011 until January 2021 for English literature. Thereafter, we sifted out randomized controlled trials (RCTs) which compared different interventions schemes for the pain management after shoulder arthroscopy and selected only 12h, 24h or 48h after the patient leaves the operating room as optimal period for administration of analgesia intervention schemes. Only patients with shoulder disease who have undergone arthroscopic shoulder surgery were included in this study. The Cochrane “risk of bias” was used for the quality assessment. Moreover, some additional tests were performed to enhance the credibility of the results. Results: Twenty-nine RCTs involving 1885 patients were included in this frequentist network meta-analysis. These articles mainly were divided into two distinct groups: nerve block group and non-nerve block group. Regarding nerve block group, at postoperative 12h, the intervention suprascapular nerve block + interscalene nerve block (SSNB+INB) was ranked first, whereas interscalene nerve block+ intra-articular injection (INB+IAI) was ranked first at 24h and 48h post operation. In the non-nerve block group, external application (EA) was ranked first at postoperative 12h, but oral administration (OA) exhibited better analgesic effect at postoperative 24h and postoperative 48h. Conclusion: We conclude that the analgesic effect of SSNB+INB was the best at postoperative 12 h, and INB+IAI was the best at postoperative 24h and 48 h in the nerve block group. For the non-nerve block group, the effect of EA was the best at postoperative 12h, and the analgesic effect of OA at postoperative 24h and 48h was significantly better than any other interventions.